2001
DOI: 10.1021/bi010272u
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Irreversible G Protein Alpha Subunit Misfolding Due to Intramolecular Kinetic Bottleneck that Precedes Mg2+ “Lock” after GTP/GDP Exchange

Abstract: Stoichiometric exchange of GTP for GDP on heterotrimeric G protein alpha (Galpha) subunits is essential to most hormone and neurotransmitter initiated signal transduction. Galphas are stably activated in a Mg2+ complex with GTPgammaS, a nonhydrolyzable GTP analogue that is reported to bind Galpha, with very high affinity. Yet, it is common to find that substantial amounts (30-90%) of purified G proteins cannot be activated. Inactivatable G protein has heretofore been thought to have become "denatured" during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
6
12
0
Order By: Relevance
“…The loss in intensity is consistent with the release of Gα i3 •GDP•AlF 4 − (curve a in Figure 2B). Interestingly the fast component decay is comparable to the result obtained by Sarvazyan et al [26], while the slow dissociation was comparable to the measurements of Zelent et al [27]. Our data appear to suggest two distinct populations of G proteins that display different levels of reactivity.…”
Section: Guanine Nucleotide Activation Of the Heterotrimeric Gαβγ Comsupporting
confidence: 91%
See 1 more Smart Citation
“…The loss in intensity is consistent with the release of Gα i3 •GDP•AlF 4 − (curve a in Figure 2B). Interestingly the fast component decay is comparable to the result obtained by Sarvazyan et al [26], while the slow dissociation was comparable to the measurements of Zelent et al [27]. Our data appear to suggest two distinct populations of G proteins that display different levels of reactivity.…”
Section: Guanine Nucleotide Activation Of the Heterotrimeric Gαβγ Comsupporting
confidence: 91%
“…Figure 1A shows the binding of fluorescein-labeled α i3 subunits to βγ subunits on beads (K D ≈ 32nM). This value is within the range of affinity constants for the interaction between α and βγ previously reported to vary from subnanomolar to tens of nM depending on experimental conditions and type of subunit [26,27]. Figure 1B shows the comparative influence of α i2 and α i3 subunits with respect to the equilibrium binding of the ligand activated FPR.…”
Section: The Assembly Of Heterotrimeric Gαβγ and Ternary Lrg On Beadssupporting
confidence: 75%
“…extent. Subsequent biophysical investigations suggest that the nucleotide-free form of the G protein is the most conformationally dynamic and is destabilized relative to the GDP-or GTP-bound forms; however, it retains an intact fold competent for signaling (62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that the ␣ T *(S43N) mutant stabilizes the ternary complex, such that it persists even following GDP-GTP exchange on ␣ T *(S43N). It has been shown that the binding of Mg 2ϩ is essential for the enhancement in intrinsic trytophan fluorescence that accompanies the conformational change in Switch 2 that occurs upon the activation of retinal ␣ T (44). In the case of the ␣ T *(S43N) mutant, we observe changes in its intrinsic tryptophan fluorescence upon binding GTP␥S, but these changes are substantially smaller than those for wildtype ␣ T *.…”
Section: Discussionmentioning
confidence: 63%